2023
DOI: 10.1001/jamanetworkopen.2023.29186
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features of Resected Melanoma Brain Metastases, Clinical Outcomes, and Responses to Immunotherapy

Harish N. Vasudevan,
Cyrille Delley,
William C. Chen
et al.

Abstract: ImportanceCentral nervous system (CNS)–penetrant systemic therapies have significantly advanced care for patients with melanoma brain metastases. However, improved understanding of the molecular landscape and microenvironment of these lesions is needed to both optimize patient selection and advance treatment approaches.ObjectiveTo evaluate how bulk and single-cell genomic features of melanoma brain metastases are associated with clinical outcome and treatment response.Design, Setting, and ParticipantsThis coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…SCS is employed by researchers to understand the type, number, and functional status of tumor immune cells. Analysis of immune cells in melanoma patients has shown that the diversity of tumor-infiltrating T cells is closely related to survival, providing an important basis for individualized immunotherapy ( Li et al, 2022 ; Vasudevan et al, 2023 ). Resistance of tumor cells to chemotherapeutic drugs is a considerable challenge in clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…SCS is employed by researchers to understand the type, number, and functional status of tumor immune cells. Analysis of immune cells in melanoma patients has shown that the diversity of tumor-infiltrating T cells is closely related to survival, providing an important basis for individualized immunotherapy ( Li et al, 2022 ; Vasudevan et al, 2023 ). Resistance of tumor cells to chemotherapeutic drugs is a considerable challenge in clinical treatment.…”
Section: Discussionmentioning
confidence: 99%